2016
DOI: 10.1016/j.bbi.2015.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen protects the blood–brain barrier from inflammation-induced disruption and increased lymphocyte trafficking

Abstract: Sex differences have been widely reported in neuroinflammatory disorders, focusing on the contributory role of estrogen. The microvascular endothelium of the brain is a critical component of the blood-brain barrier (BBB) and it is recognised as a major interface for communication between the periphery and the brain. As such, the cerebral capillary endothelium represents an important target for the peripheral estrogen neuroprotective functions, leading us to hypothesise that estrogen can limit BBB breakdown fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 48 publications
4
109
0
Order By: Relevance
“…Females had lower BBBP in our study, which was consistent with a previous study 9. An animal study demonstrated estradiol could prevent inflammation-induced tight junction breakdown by regulating inter-endothelial cell permeability and limiting the transmigration of lymphocyte 28. Hence, females might benefit from the protective effect of estradiol on BBB.…”
Section: Discussionsupporting
confidence: 92%
“…Females had lower BBBP in our study, which was consistent with a previous study 9. An animal study demonstrated estradiol could prevent inflammation-induced tight junction breakdown by regulating inter-endothelial cell permeability and limiting the transmigration of lymphocyte 28. Hence, females might benefit from the protective effect of estradiol on BBB.…”
Section: Discussionsupporting
confidence: 92%
“…The exact mechanism of AnxA1 on IFX effects is not well understood, but a prominent role of AnxA1 on epithelial integrity is hypothesized, as AnxA1 promotes proliferation and migration of epithelial cells, playing an important role in tissue regeneration [19,20]. Moreover, this supports tight junction integrity, such as in the bloodbrain-barrier [28][29][30]. Furthermore, we speculate that the preservation of the epithelial layer by IFX is not related to the direct blockade of the pro-inflammatory actions of TNF-a on the epithelial cells, but instead is indirectly linked with the AnxA1 action in protecting the mucosal histoarchitecture [19,20].…”
Section: Discussionmentioning
confidence: 97%
“…Estrogen targets the BBB by exerting protective effects (Burek et al, 2010, 2014; Suzuki et al, 2006) such as up‐regulating proteins involved in tight junction expression. This thereby limits barrier permeability (Maggioli et al, 2016; Nadkarni and McArthur, 2013). Whether the females in the current study display higher up‐regulation of tight junction proteins relative to their male counterparts warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%